PELATIHAN MEMBUAT MEDIA PEMBELAJARAN MULTIMEDIA BAGI GURU-GURU DI SD MUHAMMADIYAH IV KOTA PADANG - Dini Susanti Dini Susanti; Ridania Ekawati (Menara Pengabdian, 2021)
SD Muhammadiyah IV Padang City is an educational institution located at Jln Sawahan No.103, Simpang Haru, Kec. East Padang, Padang City Prov. West Sumatra. Teaching and learning activities at SD Muhammadiyah IV Padang City have used Curriculum 13. The problem with partners raised in this community service program is the lack of maximum knowledge of teachers about Curriculum 13 at partner schools. Constraints that are often experienced by partners are in learning tools, especially in the models and learning media used. In addition, the lack of teacher knowledge by combining Curriculum 13 with learning media. In relation to the main problems that have been mentioned, this program will offer solutions that are expected to solve partner problems.The method used is a participatory approach, which is an approach that is oriented to efforts to increase the participation of teachers directly in making multimedia learning media. The participatory approach in essence can be interpreted as an effort or way to involve teachers in learning activities which include three stages, namely the program planning stage, program implementation and program assessment.The result of this community service program is that partners will have multimedia learning media. In addition, another result is an increase in learning tools in accordance with Curriculum 13. And schools (principals and teachers) can use the media in their respective classes. The results of this service will be published in an accredited national journal. The rest will be teaching materials for MI/SD Social Studies courses at PGMI FAI UMSB Keywords –Media, Learning, Multimedia, Approach, Participatory